Modalités de diffusion et rhétoriques des discours misogynes et misogames imprimés à la Renaissance - Tatiana Clavier (Glad!)
From the end of the fifteenth until the end of the sixteenth centuries, the first printing press allowed for the publication of various discourses aiming at attacking or defending. Women’s situation and rights was strongly worsening since the end of the thirteenth century with the clergy getting greater power. Meanwhile, women leaders at the head of the State defended their cause, as women of the Grand Duchies had done before them, by supporting the first outbursts of the Quarrel about Women. The first misogynistic and misogamistic printed discourses were sometimes published under misleading titles or together with inconsistent speeches, always triggering numerous retaliations. Rhetorics in favour of women were sufficiently widespread to appear in advocates of the gender order’s discourses. Not only misogynistic writers contested or scoffed at arguments in favour of women, but the most virulent among them also pretended to be alongside women or found excuses to disparage them. These inconsistencies in misogynistic speeches attest to the power of the feminist arguments at the time of the first printing press, concomitant with the intensification of the Quarrel about Women.